2019
DOI: 10.4103/ijmr.ijmr_984_18
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin levels after laparoscopic sleeve gastrectomy in obese individuals

Abstract: Background & objectives: Ghrelin is an orexigenic gut hormone expressed by the gastric fundus. Laparoscopic sleeve gastrectomy (LSG) procedure involves resection of the gastric fundus leading to a decreased appetite and weight loss. This study was undertaken to determine the levels of plasma ghrelin after sleeve gastrectomy in obese patients. Methods: The study was conducted on 90 morbidly obese patients [body mass index (BMI) >40 kg/m 2 ] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…They also found an increase in plasma ghrelin levels after weight loss induced by caloric restriction, suggesting that GB bypass itself is associated with decreased levels of circulating ghrelin. However, a study carried out by Sharma et al, (2019) found a significant weight loss and decrease in BMI at three and six months postoperatively after SG. This difference may be attributed to in the current study we did not study the rhythm of ghrelin after two months [19] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They also found an increase in plasma ghrelin levels after weight loss induced by caloric restriction, suggesting that GB bypass itself is associated with decreased levels of circulating ghrelin. However, a study carried out by Sharma et al, (2019) found a significant weight loss and decrease in BMI at three and six months postoperatively after SG. This difference may be attributed to in the current study we did not study the rhythm of ghrelin after two months [19] .…”
Section: Discussionmentioning
confidence: 92%
“…However, a study carried out by Sharma et al, (2019) found a significant weight loss and decrease in BMI at three and six months postoperatively after SG. This difference may be attributed to in the current study we did not study the rhythm of ghrelin after two months [19] .…”
Section: Discussionmentioning
confidence: 92%
“…It is known that, under normal conditions, ghrelin production in the stomach and secretion into the blood are decreased during satiety, while production increases during fasting and starvation, resulting in an increase in ghrelin concentration in the blood [ 26 ]. Conversely, blood ghrelin concentration and appetite have been found to be decreased in patients who have been administered with anticancer drugs, patients with gastric mucosal atrophy or gastrectomy [ 42 , 43 , 44 , 45 ], and in animal models of these conditions [ 22 , 46 , 47 , 48 , 49 ]. Blood ghrelin levels have been found to be reduced in mice treated with the anticancer drug cisplatin [ 46 , 47 ] and classical SSRIs [ 49 ], as well as during psychological stress [ 22 ] and cancer cachexia [ 48 ].…”
Section: Abnormal Ghrelin Secretion and Changes In Reactivitymentioning
confidence: 99%
“…This type of cell produces the appetite-stimulating hormone ghrelin. Ghrelin production is suppressed following LSG, leading to decreased stimulation of the hunger center [ 21 ].…”
Section: Gastroesophageal Reflux Disease and Laparoscopic Sleeve Gastrectomymentioning
confidence: 99%